Розвиток мотивації учіння студентів в контексті активізації навчання - Зайцева, І.В. (Інститут літератури ім. Т.Г. Шевченка НАН України, 2009)
В статье рассматриваются основные теоретические положения формирования мотивации учения студентов, определены уровни развития мотивации учения, а также дано их психолого-педагогическое обоснование. The article deals with fundamental theoretical statements in the sphere of formation of students’ learning motivation, the levels of formation of students’ learning motivation are defined and also their psychological and pedagogical argumentation is given.